INOVASI PACKAGING PRODUK DOMBA KALENG UNTUK MENINGKATKAN EKONOMI UMKM DI MT FARM DESA TEGAL WARU FARMLAND - Mursyidah, Azizah; Bayu Purnama; Abrori; Nugroho; Zompi (Sahid Mengabdi: Jurnal Pengabdian Masyarakat Institut Agama Islam Sahid Bogor, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in the Indonesian economy, but often face challenges in product innovation and marketing. MT Farm, an MSME in Tegal Waru Farm Land Village, has developed canned lamb product innovation to increase added value and competitiveness. This product is processed using autoclave technology, making it durable and easy to distribute. This community service aims to assist MT Farm in marketing canned lamb products through training and mentoring. The results of the community service show an increase in the knowledge and skills of MT Farm staff, an increase in product quality, an expansion of market reach, and an increase in sales. Canned lamb product innovation is expected to improve the MSME economy and community welfare.